What We Know About Cardiac Function of Our Retired People - Khan, AKM Hafiz Uddin; Latif, Shah Abdul (Journal of Bangladesh Society of Physiologist, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Background: Bangladesh is one of the twenty countries in the world with the largest elderly populations, and by 2025, along with four other Asian countries, will account for 44% of world's total elderly population. This rapidly increasing population is a new and important group in terms of social and health policy in the country. As retired geriatric population is increasing day by day and there is a striking increase in their life expectancy and age is a key risk factor for coronary artery disease and because morbidity and mortality from coronary artery diseases increase with age. so evaluation of the cardiac function of retired persons are essential. Objective: To analyze the cardiovascular function of retired geriatric population in terms of measurement of ejection fraction by echocardiography. Design: This was a cross-sectional study. Participants: 70 Retired persons aged 57 years and above without known hypertension, diabetes, renal diseases as study group and 70 healthy adult aged 18-55 years as control group were included in this study. All were obtained from different areas of greater Mymensingh districts of Bangladesh. Intervention: Ejection fraction by echocardiography. Out come measures: Ejection fraction fraction %. Results: Significant decrease of ejection fraction was found in the study group( 57 years and above) in comparison to control group.(P < 0.01) The mean ejection fraction in different age group shows that there is decrease in ejection fraction of study groups than the control groups irrespective of age. Limitation: There was scarcity of Echocardiography at Mymensingh Medical College Hospital. Color doppler echocardiograph was poorly available at the present settings. So diastolic function can not be assessed. Conclusion: Though the mean ejection fraction value was significantly decreased in 57 years and above, which was progressively decreased by age, yet nearly all the values(2.72%) were within normal physiological limits. So, it seems that the retired geriatric population was having good cardiac function in our setting. Key Words : Retirement, Geriatric, Ejection fraction, Echocardiography doi: 10.3329/jbsp.v3i0.1789 J Bangladesh Soc Physiol.2008 Dec;(3):17-22.